Effect of Processing Parameters and Matrix Shrinkage on Porosity Formation During Synthesis of Metal Matrix Composites with Dual-scale Fiber Reinforcements Using Pressure Infiltration Process - (:unkn) unknown (My University, 2014)
This is first such study on porosity formation phenomena observed in dual-scale fiber preforms during the synthesis of metal matrix composites (MMCs) using the gas-based pressure infiltration process (gas PIP). In this thesis, different mechanisms of porosity formation during pressure infiltration of Al-Si alloys into Nextel's 3D woven ceramic-fabric reinforcements (a dual-porosity or dual-scale porous medium) are studied. The effect of processing conditions in terms of the infiltration temperature and pressure on porosity content of the ceramic fabric infiltrated by the alloys through the gas PIP is investigated. Relative density (RD), defined as the ratio of the actual MMC density and the density obtained at ideal 100% saturation of the preform, was used to quantify overall porosity. Increasing the infiltration temperature led to an increase in RD (and reduction in porosity) due to reduced viscosity and enhanced wettability leading to improved feedability of the liquid metal. Similarly, increasing the infiltration pressure led to enhanced penetration of fiber tows and led to higher RD and reduced porosity. For the first time, the modified Capillary number (Ca*), which is found to predict formation of porosity in polymer matrix composites quite well, is employed to study porosity in MMCs made using PIP. It is observed that in the high Ca* regime used in the present study (and common in PIP), the overall porosity shows a strong downward trend with increasing Ca* due to a decrease in the size of trapped air pockets inside fiber tows due to increased infiltration pressures. This contradicts the well-known result of increasing porosity with Ca* observed by Patel et al. in [1]. In addition, the effect of matrix shrinkage on porosity content of the samples is studied through using a zero-shrinkage Al-Si alloy as the matrix: usage of this alloy as the matrix led to a reduction in porosity content.
Keywords: Capillary Number; Dual-Scale; Metal Matrix Composite; Porosity; Pressure Infiltration Process; RTM